2011
DOI: 10.1111/j.1365-2265.2011.04165.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel mutation in the exon 2 splice donor site of the POU1F1/PIT‐1 gene in Japanese identical twins with mild combined pituitary hormone deficiency

Abstract: This is the first report of a mutation at the exon 2 donor splice site of POU1F1, affecting TAD-R2. The addition of this mutation to the growing list of pathological POU1F1 mutations may provide deeper insights into clinical heterogeneity in the expressions of individual mutations and a better understanding of the structure-function relationships of POU1F1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Therefore, mutations in exons 1 and 3-6 in POU1F1 affect both the short and long isoforms of POU1F1 protein. Only one mutation that affects exon 2 of POU1F1, namely c.214+1G>T, has been reported [7]. However, this splice donor site mutation has been shown to affect both the short and long isoforms; therefore, it is unclear whether a decrease in the function of only one of these two isoforms is sufficient for disease onset in humans.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Therefore, mutations in exons 1 and 3-6 in POU1F1 affect both the short and long isoforms of POU1F1 protein. Only one mutation that affects exon 2 of POU1F1, namely c.214+1G>T, has been reported [7]. However, this splice donor site mutation has been shown to affect both the short and long isoforms; therefore, it is unclear whether a decrease in the function of only one of these two isoforms is sufficient for disease onset in humans.…”
Section: Discussionmentioning
confidence: 96%
“…Sequencing revealed that this product corresponded to a POU1F1 transcript skipping exon 2 (Fig. 3a), which would generate Δ48-72-POU1F1, a previously reported pathogenic protein [7]. The product corresponding to the long isoform was not amplified both in controls and patients.…”
Section: Reverse Transcription (Rt) Pcrmentioning
confidence: 93%
See 2 more Smart Citations
“…POU class 1 homeobox 1 (POU1F1) is a positive pituitary specific transcription regulator for GH, PRL, and thyroid-stimulating hormone ␤ (TSH ␤), and thus it plays a key role in milk yield, growth, and fertility of livestock animals (Inoue et al, 2012). Recently, several polymorphisms of the POU1F1 pathway genes such as POU1F1, PROP1, and PITX2 genes that affect production traits have been reported both in the goat and bovine species (Daga et al, 2013;Pan et al, 2013a,b;Zhao et al, 2013).…”
Section: Discussionmentioning
confidence: 99%